2018
DOI: 10.1111/ctr.13460
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after lung transplantation for patients with occupational lung diseases

Abstract: Occupational lung diseases (OLD) including silicosis, asbestosis, and pneumoconiosis progress to end stage lung disease requiring lung transplantation (LT). Prognosis and treatment of OLDs are poorly understood and a paucity of data exists regarding LT outcomes. Additionally, transplant operative complexity for patients with OLD is high. A single center retrospective review of all single and bilateral LT recipients between May 2005 and Oct 2016 was performed. Patients were grouped by OLD, and nearest neighbor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Together, these factors stimulate the proliferation of lung fibroblasts, the production of collagen and subsequently the formation of fibrosis (2,(12)(13)(14). However, previous studies have demonstrated that antioxidants, including vitamins, carotenoids and tannins provide protection against oxidative damage, and the negative regulation of inflammatory cytokines and/or the inflammatory signaling pathway may attenuate the progression of some pulmonary diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these factors stimulate the proliferation of lung fibroblasts, the production of collagen and subsequently the formation of fibrosis (2,(12)(13)(14). However, previous studies have demonstrated that antioxidants, including vitamins, carotenoids and tannins provide protection against oxidative damage, and the negative regulation of inflammatory cytokines and/or the inflammatory signaling pathway may attenuate the progression of some pulmonary diseases (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no specific treatment for silicosis. The current treatment procedure involves removing the exposure of silica particles and symptomatic treatment . Accumulated evidence has revealed that the process of silicosis involves multiple signaling pathways, which regulate various cellular events, such as the persistent inflammatory response and structural destruction of lung tissues, and finally lead to respiratory failure .…”
Section: Discussionmentioning
confidence: 99%
“…LTx is an option for several other ILDs including Langerhans cell histiocytosis [67], occupational ILD including silicosis [68,69], pleuroparenchymal fibroelastosis (PPFE) [70], chronic hypersensitivity pneumonitis [71] and sarcoidosis. Sarcoidosis is the most common of these less-frequent indications for LTx, accounting for 2.4% of worldwide transplants between 1995 and 2018 [1].…”
Section: Considerations In Other Ilds Including Sarcoidosismentioning
confidence: 99%
“…Evaluation of LTx candidacy is also similar, although surgical complexity can be increased in those with dense pleural adhesions. For example, one study compared outcomes of LTx for occupational lung disease versus other diagnoses, and demonstrated similar long-term survival, but a higher need for cardiopulmonary bypass and delayed chest closure in the occupational lung disease cohort [69]. PPFE, presenting either as its own entity or co-existing with other patterns of ILD, can be particularly challenging operatively, with dense adhesions often leading to thoracic contraction and increased bleeding risk [76].…”
Section: Considerations In Other Ilds Including Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation